The Impact of Australian Consumer Price Index on the Exchange Rate of Australian Dollar - Chinese Renminbi - Maoguo Wu; Yue Yu (European Scientific Journal, ESJ, 2017)
This paper investigates the impact of Australian consumer price index on Australian dollar - Chinese renminbi exchange rate. As two major economies in Asia Pacific, China and Australia are conducting ever-increasing volume of economic transactions. Massive Chinese investment, particularly in properties, has caused steady increase in Australian consumer price index and the exchange rate of Australian dollar - Chinese renminbi. Recent slowdown of Chinese economic growth and Chinese investment in Australia caused both Australian consumer price index and the exchange rate of Australian dollar - Chinese renminbi to fall significantly. This paper utilizes data from May 2005 to January 2016 and empirically tests the relation between Australian consumer price index and the exchange rate of Australian dollar - Chinese renminbi. In compliance with classical theories of exchange rates, empirical results find that a negative relation exists between Australian consumer price index and the exchange rate of Australian dollar - Chinese renminbi.